PENGARUH SERTIFIKAT BANK INDONESIA SYARIAH (SBIS) DAN PASAR UANG ANTAR BANK SYARIAH (PUAS) TERHADAP INDEKS PRODUKSI INDUSTRI (IPI) DI INDONESIA TAHUN 2017-2021 - Fatimah, Sit (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The Industrial Production Index (IPI) is a macroeconomic indicator to monitor the progress of industrial sectors in the Indonesian economy. The development of IPI in Indonesia from 2017-2021 has increased. This increase in IPI certainly has factors that influence it, one of which is Bank Indonesia policy through monetary policy through sharia Open Market Operation activities using the Bank Indonesia Sharia Certificate (SBIS) and Sharia Interbank Money Market (PUAS) instruments. In theory, Fakhruddin and Daniar state that the Bank Indonesia Sharia Certificate and the Sharia Interbank Money Market will encourage growth in the Industrial Production Index. However, in the data studied, the Bank Indonesia Sharia Certificate data appears to tend to fluctuate and the Sharia Interbank Money Market data tends to experience an increase that is not in line with the increase in the value of the Industrial Production Index. This research is quantitative research. The data used is time series data. The data source used is secondary data, in the form of documentation data or monthly financial report data published by the Financial Services Authority and the Central Statistics Agency from 2017-2021. And the sample in this study consisted of 60 samples. The data analysis technique used is Eviews Version 12. Based on partial research results, the Bank Indonesia Sharia Certificate has no effect on the Industrial Production Index. And the Sharia Interbank Money Market partially influences the Industrial Production Index. Meanwhile, simultaneously the Bank Indonesia Sharia Certificate and the Sharia Interbank Money Market have an effect on the Industrial Production Index.